PENINGKATAN KEMAMPUAN KOGNITIF MELALUI BERMAIN PLAYDOUGH - Endang Susilowati; Sumiyati Sumiyati; Subawi Subawi (Prodi Pendidikan Islam Anak Usia Dini Tarbiyah IAI Muhammadiyah Bima, 2019)
This study entitled “Cognitive Capability Enhancement Through Playdough Play For Group B Children at Tunas Bhakti Kindergarten in Tlogosari Village, Tlogowungu District, Tlogowungu District, Pati District 2016/2017. With the aim of: 1) To know cognitive abilities in TK Tunas Bhakti, TlogosariVillage, Tlogowungu District, Pati District, and 2) To find out through playing Playdough can improve cognitive abilities for group B children in Tunas Bhakti Kindergarten, Tlogosari Village, Tlogowungu District, Pati Regency . The method used is classroom action research, which consists of pre-cycle, cycle I and cycle II. In cycle I playing playdough with large groups and cycle II playing playdough with small groups. For this reason the teacher includes Playdough as an additional activity in cognitive development.His research findings are that media used namely media playdough little by little the cognitive of children increasingly grow and develop well. This is proven by the achievement of indicators of children’s success thatresearchers apply that is cognitive students change from stage to stage. The criteria developed very well from the pre cycle as many as 6 children or 33.33% in the first cycle were still 6 children or 33.33% and became 10 children or 55.56%. For categories developed according to expectations of 2 children or 11.11% in the first cycle to 5 children or 27.78% and in the second cycle to 8 children or 44.44%. While for the category began to develop in the pre-cycle number of 2 children or 11.11% then dropped to 1 child or 5.56%. In the second cycle there were no children who entered the category began to develop or 0%. In the undeveloped category in the pre-cycle number 8 or 44.44%, then in the first cycle it was reduced to 6 children or 33.33% and in the second cycle not the children who entered the undeveloped category or 0%. Based on all classroom action research activities ( PTK) it can be concluded that through playdough games can improve children’s cognitive.